PENGARUH PEMBERIAN CAMPURAN TEPUNG DAUN KELOR (Moringa oleifera Lamk.) DAN BEKATUL TERHADAP PRODUKSI ITIK PEDAGING (Anas platyrhynchos) SEBAGAI SUMBER BELAJAR BIOLOGI MATERI PERTUMBUHAN DAN PERKEMBANGAN - Asri Khoirunnisa; Agus Sujarwanta; Suharno Zen (EDUBIOLOCK, 2021)
The research about the effect of giving mixed moringa leaf flour (moringa oleifera lamk.) and rice bran to the production of broiler duck (anas platyrhynchos) as a source of learning biology material growth and development, this research aims to determine the effect of giving a mixture of moringa leaf flour (Moringa oleifera Lamk.) and rice bran on the production of broiler duck (Anas platyrhynchos), to find out the best dose of broiler duck production (Anas platyrhynchos), and to make Student Worksheet made can be used as a source of high school biology learning material for growth and development. The method used to this research is a completely randomized design (CRD), the treatment given is 4 treatments with 1 control and 3 treatments. Control (100% rice bran without moringa leaf flour), P1 (2.5 moringa leaf flour and 97.5% rice bran), P2 (5% moringa leaf flour and 95% rice bran), P3 (7.5% moringa leaf flour) and 92.5% rice bran). The parameters observed in this research were the weight and length of the broiler ducks (Anas platyrhynchos). The results of the research were tested using a parametric statistical test or what is commonly called the one-way ANOVA test, from this test the hypothesis h0 is accepted for the weight / weight of broiler ducks, the hypothesis h0 is accepted because fcount = 4,66 > ftabel = 2.95, this one-way ANOVA test shows no significant difference. of the four feed mixtures. whereas the h0 hypothesis was accepted for broiler duck body length, the h0 hypothesis was accepted because fcount = 4,58 > ftabel = 2.95, this one-way ANOVA test showed no significant difference between the four feed mixtures. The conclusion that no effect on the production of broiler ducks (Anas platyrhynchos). but in biology there is any effect 1113,38gr. The SWS (Student Worksheet) has used as a learning resource for high school biology on growth and development material.